2019
DOI: 10.1002/inf2.12055
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale control of grain boundary potential barrier, dopant density and filled trap state density for higher efficiency perovskite solar cells

Abstract: In this work, grain boundary (GB) potential barrier ( Δφ GB), dopant density (Pnet), and filled trap state density (PGB,trap) were manipulated at the nanoscale by exposing the fabricated perovskite films to various relative humidity (RH) environments. Spatial mapping of surface potential in the perovskite film revealed higher positive potential at GBs than inside the grains. The average Δφ GB, Pnet, and PGB,trap in the perovskite films decreased from 0% RH to 25% RH exposure, but increased when the RH increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 64 publications
(195 reference statements)
0
18
0
Order By: Relevance
“…Several metal-oxide based semiconductors, such as titanium dioxide (TiO 2 ) [ 15 , 16 , 17 , 18 ], zinc oxide (ZnO) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], copper oxide (CuO) [ 28 , 29 , 30 , 31 ], zirconium oxide or zirconia (ZrO 2 ), cerium oxide (CeO 2 ) [ 29 ], tungsten oxide (WO 3 ), and tin oxide (SnO 2 ), have been successfully demonstrated as efficient photocatalysts for pollutant removal [ 32 , 33 , 34 ] and utilized in several other applications (energy, environment, and health) [ 35 , 36 , 37 ]. The semiconductor photocatalytic process includes irradiation of the semiconductor surface with a light having energy greater than the semiconductor’s bandgap.…”
Section: Introductionmentioning
confidence: 99%
“…Several metal-oxide based semiconductors, such as titanium dioxide (TiO 2 ) [ 15 , 16 , 17 , 18 ], zinc oxide (ZnO) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], copper oxide (CuO) [ 28 , 29 , 30 , 31 ], zirconium oxide or zirconia (ZrO 2 ), cerium oxide (CeO 2 ) [ 29 ], tungsten oxide (WO 3 ), and tin oxide (SnO 2 ), have been successfully demonstrated as efficient photocatalysts for pollutant removal [ 32 , 33 , 34 ] and utilized in several other applications (energy, environment, and health) [ 35 , 36 , 37 ]. The semiconductor photocatalytic process includes irradiation of the semiconductor surface with a light having energy greater than the semiconductor’s bandgap.…”
Section: Introductionmentioning
confidence: 99%
“…For example, through the tunability of RH, PSCs give disparate J–V curves fabricated at 0%, 25%, 35%, and 45% RH ( Figure a). [ 215 ] Here, the PCE of PSCs prepared under 25% RH is the highest, which gives the smallest average GB potential barrier, dopant density, and filled trap‐state density, with values of 20.17 meV, 3.72 × 10 15 cm −3 , and 4.37 × 10 10 cm −2 , respectively, almost half of that under 0% RH. The mechanism of improved performance under humidity is attributed to the enhanced reconstruction principle [79b] .…”
Section: Design Strategies For Scsmentioning
confidence: 96%
“…Reproduced with permission. [ 215 ] Copyright 2019, Wiley‐VCH. b) SEM images of PCBM via evaporated and spun syntheses, respectively.…”
Section: Design Strategies For Scsmentioning
confidence: 99%
“…A large number of hydrated crystals appear between grains due to the faster diffusion of water molecules along grain boundaries. 61,65 MAPbI 3 ÁH 2 O with a wide band gap of 3.1 eV blocks the transport of carriers, causing a sharp drop in photocurrent. However, Leguy et al reported that hydration can be fully repaired after the device under dry nitrogen for several hours, and the presence of liquid water will make hydration process irreversible.…”
Section: The Influence Of Environment On the Stability Of Halide Pementioning
confidence: 99%